Some geographical and geological aspects in Johann Forster’s posthumous journals… controversy – HMS resolution memoirs never refined - Vorbrich, Krzysztof K. (Quaestiones Geographicae, 2022)
The article takes part in the controversy surrounding the scientific heritage of Johann Forster born in Poland, of Scottish ancestry, writing in Latin, German and English. The main medium are Johann’s Journals drafted in English during Cook’s Second Circumnavigation. This article first presents the scientific controversy surrounding the posthumously published Journals… Then in eleven topic-organised sections it depicts critically the geographical and geographo/geological character of these diaries.